Optical Coherence Tomographic Observation of Morphological Features of Neointimal Tissue after Drug-Eluting Stent Implantation - Lee, Seung-Yul (Yonsei University College of Medicine, 2014)
PURPOSE: The impacts of different time courses and the degree of neointimal growth on neointimal morphology have not yet been sufficiently investigated. Therefore, we evaluated the morphological features of neointimal tissue after drug-eluting stent (DES) implantation using optical coherence tomography (OCT). MATERIALS AND METHODS: The morphological features of neointimal tissue in stented segments with a maximal percentage of cross-sectional area (CSA) stenosis of neointima were evaluated in 507 DES-treated lesions with >100 µm mean neointimal thickness on follow-up OCT. Neointimal tissue was categorized as homogeneous, heterogeneous, layered, or neoatherosclerotic. RESULTS: In lesions with <50% of neointimal CSA stenosis, homogeneous neointima (68.2%) was predominant, followed by heterogeneous neointima (14.1%) and layered neointima (14.1%). In lesions with ≥50% of neointimal CSA stenosis, layered neointima was most frequently observed (68.3%), followed by neoatherosclerotic neointima (25.2%). In subgroup analysis of lesions with ≥50% of neointimal CSA stenosis, 89.5% of the lesions with a stent age <30 months were layered neointima, while 62.3% of the lesions with a stent age ≥30 months were neoatherosclerotic neointima. CONCLUSION: This study suggests that the OCT-detected morphology of DES neointimal tissue was different according to the follow-up time course and degree of neointimal hyperplasia.